Upconversion amplification through dielectric superlensing modulation - Liangliang Liang (Nature Portfolio, 2019)
Emission levels useful for applications from upconversion nanoparticles require high laser irradiance. Here, Liang et al. exploit the superlensing effect from dielectric microbeads to enhance the luminescence efficiency of upconversion nanoparticles and show its application for optogenetics.